Guidelines for Super Leadership Development of School Administrators under Roi-Et Secondary Educational Service Area Office, Thailand - Srichuen , Jirattikorn; Ruangsuwan, Chayakan; Phujomjit , Pongphop (Journal for Developing the Social and Community, 2025)
Background and Aims: In the 21st century, developing school administrators with Super Leadership is essential to enhancing the quality of education. This leadership style focuses on empowering followers to become effective self-leaders. The objectives of this study were (1) to investigate the current and desired states as well as the priority needs of super leadership among school administrators under the Secondary Educational Service Area Office Roi Et, and (2) to develop practical guidelines for strengthening super leadership appropriate to the school context. Methodology: This research employed a Research and Development (R&D) design consisting of two phases. Phase 1 (quantitative) used a questionnaire administered to 345 participants selected through stratified random sampling by school size. Phase 2 (qualitative) employed semi-structured interviews with six outstanding school administrators and evaluations from nine experts. Data was analyzed using descriptive statistics (Mean, Standard Deviation and PNIModified index) and content analysis. Results: (1) The current state of super leadership was rated at a high level, while the desired state was at the highest level. The most critical need was promoting staff self-leadership. (2) The developed guideline consisted of seven components: promoting self-leadership, role modeling, self-goal setting, positive thinking, constructive feedback and rewards, teamwork, and fostering a self-leadership culture. Expert evaluations indicated that the guidelines were highly appropriate and feasible. Conclusion: The proposed super leadership development guideline is practical and contextually applicable for Thai schools. It enables educational administrators to act as change leaders who empower teachers to become self-directed, thereby fostering sustainable learning organizations.